Barriers to health in women of reproductive age living with or at risk of non-communicable diseases in Nigeria: a Photovoice study - Imo Etuk; Amira Iwuala; Kendra Njoku; Bosoye Olagbegi; Ayoposi Ogboye; Jonas Kofi Akpakli; Ugo Okoli; Kathleen Hill; Oniyire Adetiloye; Donald Imosemi; Victoria Omoera; Folashade Oludara; et al. (BMC, 2023)
Abstract Background Nigeria has one of the highest maternal mortality ratios (MMR) globally with an MMR of 512 (per 100,000 live births) and the proportion of maternal deaths due to non-communicable diseases (NCDs) is increasing. While evidence shows that many of these deaths are preventable, limited attention is being paid to the unique vulnerabilities and experiences of women of reproductive age (WRA) with NCDs and their risk factors, as well as the barriers to the screening, diagnosis, and management of these diseases in Nigeria. Methods This study explored the lives of WRA in Lagos and Federal Capital Territory in Nigeria from May to June 2019 using a community-based participatory research (CBPR) methodology called Photovoice which is aligned with CBPR as it includes procedures such as the identification of important community issues, discussion of photo assignments and data analysis. Twenty-four women of reproductive age were provided with digital cameras and trained on how to capture photos that conveyed their current health, healthcare utilization and engagement, and experience journeys. Individual interviews with the women were held for an in-depth exploration of the photographs. The data was then analysed thematically. Results Six distinct themes were identified across the barriers highlighted by the women: food and nutrition, home and family, neighborhood-built environment, economic instability, religion and spirituality and low prioritization of self-care. These themes captured the challenge of reduced agency, limited contribution and participation, and a complex relationship between visible and invisible illness. Conclusion The perspectives of WRA in Nigeria obtained through this qualitative research provided a strong substratum for understanding the environmental barriers that predispose WRA to NCDs in Nigeria. The results of the study are useful for the improvement of woman-centred services of prevention, diagnosis, and management of NCD risk factors across the maternal and reproductive health care continuum in Nigeria.